The role of the biofilm and the crowded motility of Proteus bacteria in patients with catheter-associated urinary tract infection. (Journal of the College of Basic Education, 2022)
110 urinary sample were collected from urethral catheters of patients who had admitted to the intensive care units in 3 hospitals in Baghdad(Surgical subspecialities hospital/ Medical city, Al-Kindy teaching hospital & Ibn Al-Kuff hospital) during the period between October 2013 & January 2014, Proteus spp. Was present in 20 urinary samples (24.3%) and Proteus mirabilis represented 20 strains (100%). The effect of antibiotics on bacterial strains was investigated using AST-card and the results revealed differences in the resistance of strains to the 20 chosen antibiotics, , while some strains have shown multidrug resistance to 7-14 antibiotics (64.3%).The 20 strains of Proteus mirabilis have shown an ability to form biofilm in a rate of 100% but with variable degrees. The Biofilm was highly produced by 10 strains (50%), the other 10 strains have shown low ability to produce the biofilm.Multiple concentrations of alcoholic extract of Laurus nobilis were prepared & their effect on the studied dacteria strains was investigated. It was noticed that the concentration of 200 mg/ml had given the highest area of inhibition (20 mm) , while the concentration of 6.25 mg/ml had given the lowest area of inhibition (10 mm).The effect of lactoferrin solution on the 20 strains of Proteus mirabilis was investigated and the results revealed that the concentration of 200 mg/ml had given an area of inhibition of 7 mm before performing solution dialysis whereas after dialysis and decreasing volume to the half , the area of inhibition increased to 15 mm.The minimal inhibitory concentration (MIC) , & the biofilm inhibitory concentration for both of alcoholic extract of Laurus nobilis & lactoferrin solution were quantified , and the results have shown that MIC of alcoholic exract of Laurus nobilis & lactoferrin was 6.25 & 100mg/ml respectively whereas BIC of alcoholic extract & lactoferrin was 100 & 200 mg/ml respectively.The effect of BIC of alcoholic exract & lactoferrin on the inhibition of adhesion of biofilm of Proteus mirabilis was investigated using microtiter plate method , the rate of 8-43%for alcoholic extract, & 18-59% for lactoferrin solution .The BIC of alcoholic extract of Laurus nobilis & lactoferrin solution were adopted in investigating the inhibition of adhesion into catheter tubes of Proteus mirabilis and other types of gram negative bacteria isolated from urethral catheters.BIC was also adopted for inhibition of swarming phenomena where the results have shown significant removal of biofilm from catheter tubes when seen by naked eye compared to control, as well as inhibition of swarming phenomena compared to control.Five strains of Proteus mirabilis were selected according to their high rate of production of biofilm , for molecular & genetic study to discover the virulence factors responsible for biofilm production. PCR technology was used to demonstrate one of the most important virulence factors which is (fimbriae) responsible for bacterial adhesion on the surfaces of lining epithelium of urinary tract and catheter tnbes which leads to biofilm production .The results have shown that all the selected five strains had PMF gene which is responsible for fimbriae encoding , were the volume of primer was (618 bp) for all the five strains ; the five strains have given a positive results (100%) in the same path of ladder of band (600bp) when examined by electrophoresis